Effects of short-chain fatty acids on intestinal function in an enteroid model of hypoxia - Pearce, Sarah C.; Karl, J. Philip; Weber, Gregory J. (Frontiers in Physiology, 2022)
The healthy GI tract is physiologically hypoxic, but this may be perturbed by acute and chronic stressors that reduce oxygen availability systemically. Short-chain fatty acids have been shown to have beneficial effects on intestinal barrier function and inflammation. Therefore, our objective was to see whether short-chain fatty acids (SCFA) would improve GI barrier function, reduce pro-inflammatory cytokines, and increase the expression of genes regulating GI barrier function in enteroids exposed to hypoxia. Human duodenal enteroid monolayers were placed under hypoxia (1.0% O2) for 72h with either 24, or 48 h pre-treatment with a high acetate ratio of SCFA’s or high butyrate ratio or placed under hypoxia concurrently. Transepithelial electrical resistance (TEER) increased with SCFA pre-treatment, especially 48 h of pre-treatment and this was maintained through the first 48 h of hypoxia while cells saw barrier function dramatically decrease by 72 h of hypoxia exposure. Inflammatory protein secretion largely decreased with exposure to hypoxia, regardless of SCFA pre-treatment. Gene expression of several genes related to barrier function were decreased with exposure to hypoxia, and with concurrent and 24 h SCFA pre-treatment. However, 48 h SCFA pre-treatment with a high butyrate ratio increased expression of several metabolic and differentiation related genes. Overall, pre-treatment or concurrent treatment with SCFA mixtures were not able to overcome the negative impacts of hypoxia on intestinal function and cells ultimately still cannot be sustained under hypoxia for 72 h. However, 48 h pre-treatment maintains TEER for up to 48 h of hypoxia while upregulating several metabolic genes.